1980
DOI: 10.1002/art.1780230710
|View full text |Cite
|
Sign up to set email alerts
|

Chronic arthritis of rabbits induced by mycoplasmas II.antibody response and the deposition of immune complexes

Abstract: Chronic mycoplasma-induced arthritis of rabbits was accompanied by a highly active humoral immune response. Peak antibody titers coincided with the "disappearance" of mycoplasmas from joint tissues at 7 weeks. High synovial fluid antibody titers and immunoglobulin-producing cells in frozen sections of synovial membrane suggested local antibody production. Persistence of granular deposits containing IgG and complement in synovium and cartilage may be a mechanism for continuing inflammation in the apparent absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

1982
1982
2002
2002

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…We previously suggested (7) that the pathogenesis of M arthritidis-induced arthritis of rabbits might be similar to that proposed by Cooke et a1 for experimental antigen-induced arthritis (8)(9)(10). Chronic antigen-induced arthritis results when an animal that has been preimmunized with an antigen in complete Freund's adjuvant is challenged intraarticularly with the same antigen in an aqueous medium (1 I).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We previously suggested (7) that the pathogenesis of M arthritidis-induced arthritis of rabbits might be similar to that proposed by Cooke et a1 for experimental antigen-induced arthritis (8)(9)(10). Chronic antigen-induced arthritis results when an animal that has been preimmunized with an antigen in complete Freund's adjuvant is challenged intraarticularly with the same antigen in an aqueous medium (1 I).…”
supporting
confidence: 62%
“…We have shown that Mycoplasma arthritidis, which causes arthritis in rats (1,2) and mice (3,4), also induces arthritis in rabbits after intraarticular injection (5)(6)(7). Although the rabbit disease can last as long as 1 year, neither viable organisms nor mycoplasmal antigens appear to persist in joint tissues longer than a few weeks.…”
mentioning
confidence: 99%
“…IgG particles were detected in the synovial cells of chickens by an immunofluorescence technique when M. pulmonis was inoculated intraarticularly (11) or M. pulmonis periarticularly (26). Accordingly, this study demonstrated that IgGproducing cells and C3 were observed at a high frequency in the synovial membranes and perisynovial tissues over the entire period of the experiments, with concomitant presence of mycoplasmal particles in macrophages.…”
Section: Serological Findingsmentioning
confidence: 56%
“…Intraarticular inoculation caused clinical and histopathological changes in the injected joints which were much more evident than those in the other joints. Washburn et al (26,27) reported the deposition of immunoglobulins, a complement and mycoplasma cells in synovial membranes in rabbits intraarticularly inoculated with M. pulmonis or M. arthritidis. Snick and Coulie (19) and Nemazee and Sato (17) observed the appearance of the rheumatoid factor (RF) or an RF-like substance (RFLS) in mice on infection with bacteria or viruses, and stimulation of RF production by protein antigens.…”
mentioning
confidence: 99%
“…Deposits containing immunoglobulin and complement were found in joint tissues, suggesting that immune complexes may participate in the chronic phase of mycoplasma induced arthritis in rabbits. [12][13][14] Transmission electron microscopy of articular cartilage in neonatal rats infected with M pulmonis revealed the presence of mycoplasmas within the matrix and lacunae. The mycoplasmas appeared to have a tropism for the chondrocytes and induced lysis of the chondrocytes and the cartilage matrix.…”
Section: Mycoplasmal Arthritis In Animalsmentioning
confidence: 99%